athanassios veRgados, The Homeric Hymn to Hermes: Introduction, Text and Commentary. Berlin / Boston, De Gruyter, 2012, 717 pp., ISBN 978-3-11025969-8. - Taida, Ichiro (Exemplaria Classica, 2014)
(Reseña)